Biodegradation of Chlorobenzoic Acid Substitutes, Particularly, 2- Chlorobenzoic Acid by Aeromonas hydrophila (Journal of Basic and Applied Research in Biomedicine, 2022)
Bacterium Aeromonas hydrophila (A. hydrophila) was isolated from the Petra Wastewater Treatment Plant effluent in southern Jordan. It was identified by using morphological and biochemical characteristics. A. hydrophila was found to be able of using chlorobenzoate compounds as carbon and energy source. These capabilities were with different biodegradation rates (4- chlorobenzoic acid 5µM/hr, 3,4-dichlorobenzoic acid 15.5µM/hr, 2- chlorobenzoic acid 41µM/hr and 3- chlorobenzoic acid 65µM/hr). The degradation ability was monitored through the release of chloride, disappearance of the substrate and finally the growth of bacterial cells on these substrates. A. hydrophila dioxygenases physiologically induced by chlorobenzoic acid compounds, were analyzed for both ortho or meta ring-cleavage of these aromatic compounds. Only 1, 2-dioxygenase activity was detected which suggest that the cleavage is through the ortho pathway. The best results of degradation of 2-CBA compound were obtained with 3mM substrate concentration, 25ºC, pH 7and 200µl inoculum size. The carbon sources affected the 2-CBA degradation differently from that on chloride and cell mass production. Nitrogen sources used reduced the degradation activity of the 2-CBA as well as in the chlorine release from 2-CBA. However, the nitrogen source L-proline had a slight enhancement effect on the biodegradation between the 40-80h.